2018
DOI: 10.1177/0972150918812985
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Tourism and Foreign Exchange Earnings on Economic Growth in Nigeria

Abstract: Deteriorating nature experienced in the level of economic activities in Nigeria is evident in most sectors of the economy, including the tourism sector. But there is a need to develop the tourism industry because of its potentials for job creation, and the Nigerian government should make vital efforts to diversify the economy from oil production to other viable sectors in order to create wealth for the nation. Against this backdrop, this study examined the interaction effect of tourism and foreign exchange ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The Granger causality test also confirms that tourism receipt is not strong enough in Nigeria to granger cause economic growth. Unlike the findings of Tang and Abosedra (2014); Matthew et al (2018) and Omodero (2019); this finding is consistent with the results of Chiu and Yeh (2017) regarding countries that exhibited different conditions and experience on the relationship of tourism and economic growth.…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 4 more Smart Citations
“…The Granger causality test also confirms that tourism receipt is not strong enough in Nigeria to granger cause economic growth. Unlike the findings of Tang and Abosedra (2014); Matthew et al (2018) and Omodero (2019); this finding is consistent with the results of Chiu and Yeh (2017) regarding countries that exhibited different conditions and experience on the relationship of tourism and economic growth.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…In a similar study on the interaction of tourism and foreign exchange earnings on economic growth in Nigeria by Matthew et al (2018), fully modified OLS and Johansen cointegration technique were employed to analyze the time series data on GDP per capital and tourism revenue receipts for the periods of 1980 to 2016. The result of the study showed that both tourism and foreign exchange earnings have positive interactive effect on Nigerian economic growth.…”
Section: Studies On Nigerian Economiesmentioning
confidence: 99%
See 3 more Smart Citations